ASSOCIATION OF TLR2, TLR4, TLR9 GENE EXPRESSION RELATED TO INNATE IMMUNITY WITH IN VIVO ACUTE RESPIRATORY INFECTIONS CAUSED BY KLEBSIELLA PNEUMONIAE - E. V. Budanova; O. A. Svitich; E. A. Shulenina; V. V. Zverev (Медицинская иммунология)
The aim of this work was to study features of gene expression TLR2, TLR4, and TLR9 in the course of acute respiratory infection, depending on the time elapsing since the contamination, and dose of infection. The studies of in vivo models of acute respiratory infections caused by Gram-negative Klebsiella pneumoniae showed that, at infection dose of 104 CFU/ml, the TLR4 gene expression levels in epithelium of upper respiratory tract at 1, 3, 10 days were increased 30 times and more, complete elimination of the pathogen was observed at 3 days. At the dose of infection of 107 CFU/ml, persistence of the pathogen in upper respiratory tract was observed within a few days, accompanied by a significant increase in the level of TLR9 expression in epithelium of upper respiratory tract, and TLR4 levels in the lungs 1 day after infection, in parallel to elimination of the pathogen from the lower respiratory tract. Thus, the characteristic features of TLR4 and TLR9 gene expression in the upper respiratory tract may be considered a potential diagnostic and prognostic factors in evaluation of the course of acute respiratory infections caused by Klebsiella pneumoniae.